(untitled) (Praxis Educativa, 2025)
Summary The article presents results of an investigation related to the implementation of the Full Day educational policy developed in the province of Río Negro since 2013. The information obtained is focused on nine (9) primary schools in San Carlos de Bariloche belonging to the initia lgroup in which the modality was established. Ten years after the launch, in a post-pandemic time, it is interesting to carry out this work to understand and characterize the current situation. The inquirí methodology was carried out from a qualitative perspective, including group interviews with supervisors, management teams and teachers. For the analysis of the data, categories were constructed that allow the teachers experience to be characterized. Among the results, positive aspects for the training of students and difficulties in relation to infrastructure and institutional organization stand out. Guiding findings in educational policy decisión making for primary schooling.